Characterization of a plant scaffold attachment region in a DNA fragment that normalizes transgene expression in tobacco. - Breyne, P (1992)
Using a low-salt extraction procedure, we isolated nuclear scaffolds from tobacco that bind specific plant DNA fragments in vitro. One of these fragments was characterized in more detail; this characterization showed that it contains sequences with structural properties analogous to animal scaffold attachment regions (SARs). We showed that scaffold attachment is evolutionarily conserved between plants and animals, although different SARs have different binding affinities. Furthermore, we demonstrated that flanking a chimeric transgene with the characterized SAR-containing fragment reduces significantly the variation in expression in series of transformants with an active insertion, whereas a SAR fragment from the human beta-globin locus does not. Moreover, the frequency distribution patterns of transgene activities showed that most of the transformants containing the plant SAR fragment had expression levels clustered around the mean. These data suggest that the particular plant DNA fragment can insulate the reporter gene from expression-influencing effects exerted from the host chromatin.